Investigations on Suitable Configurations for Optimum Four-Bar Mechanism Balancing of Crank Rocker Engine - Abdul Halim, Ahmad Taufiq Hakim (IRC, 2018)

(untitled)
For a system to obtain perfect balancing, its external forces such as shaking forces and shaking moments are needed to be either eliminated or reduce. In this paper, numerous design approaches are modelled that theoretically will eliminate the external forces. The main objective that had been identified for the project is to determine the best configuration of a four-bar-mechanism that will produce the lowest vibration of the crank rocker engine. In our scope of study, the model is based on the design of UTP researchers single cylinder crank rocker engine mechanism. Three different models were constructed based on the initial model and counterweights are added to the links to reduce external forces. The varying parameters of all models are the value of the counterweight’s mass. Based on the data recorded in Adams’s simulation from each model, the resultant forces of magnitude were compared between the models and the best model were identified. The third design, which adds a torsional spring between the crank and rocker links proved to have the lowest force magnitude of 189.19 N after optimization process towards the counterweight’s mass. For future approaches, the proper angle of the counterweights needed to be identified for optimum results.